Effects of Robot Motion on Human-Robot Collaboration - Dragan, Anca D.; Bauman, Shira; Forlizzi, Jodi; Srinivasa, Siddhartha S. (Hri '15: ACM/IEEE International Conference on Human-Robot Interaction USB Stick, 2015)
Most motion in robotics is purelyfifnctional, planned to achieve the goal and avoid collisions. Such motion is great in isolation, but collaboration affords a human who is watching the motion and making inferences about it, trying to coordinate with the robot to achieve the task. This paper analyzes the benefit of planning motion that explicitly enables the collaborator's inferences on the success of physical collaboration, as measured by both objective and subjective metrics. Results suggest that legible motion, planned to clearly express the robot's intent, leads to more fluent collaborations than predictable motion, planned to match the collaborator's expectations. Furthermore, purely functional motion can harm coordination, which negatively affects both task efficiency, as well as the participants' perception of the collaboration.